Bovine leukemia virus small noncoding RNAs are functional elements that regulate replication and contribute to oncogenesis in vivo - Gillet, Nicolas A.; Hamaidia, Malik; Brogniez, Alix de; Gutierrez, Gerónimo; Renotte, Nathalie; Reichert, Michal; Trono, Karina Gabriela; Willems, Luc (2017)
Retroviruses are not expected to encode miRNAs because of the potential problem of self-cleavage of their genomic RNAs. This assumption has recently been challenged by experiments showing that bovine leukemia virus (BLV) encodes miRNAs from intragenomic Pol III promoters. The BLV miRNAs are abundantly expressed in B-cell tumors in the absence of significant levels of genomic and subgenomic viral RNAs. Using deep RNA sequencing and functional reporter assays, we show that miRNAs mediate the expression of genes involved in cell signaling, cancer and immunity. We further demonstrate that BLV miRNAs are essential to induce B-cell tumors in an experimental model and to promote efficient viral replication in the natural host.